Digital publics and participatory education - Brian J. McNely; Christa B. Teston; Bolutife Olorunda; Noah Dunker (Digital Culture & Education, 2010)
This article—a collaborative exploration between instructors, students, and members of the broader, digital classroom community—explores how the strategic incorporation of sociotechnical networks and digital technologies facilitates literate practices that extend the classroom in productive ways. The article builds toward coauthors’ reflective practices (Schön, 1983), or “participatory perspectives”, had during an undergraduate English Studies course at a mid-sized, public, American university. Specifically, participants argue that these literate practices afforded not just information sharing, but the opening up of a traditional classroom to include broader digital publics and collaborative knowledge work (Spinuzzi, 2006). Toward this end, we ground literate practice in scholarship that attends to public writing in online spaces, and theoretically frame our argument using Jenkins et al.’s (2006) principles of participatory education. We then detail the specific curricular approach deliberately designed to create digitally connected publics and end with generalizable significance of coauthors’ participatory perspectives.